2001
DOI: 10.1007/s004230000191
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of enterogenic endotoxinemia with lactoferrin in rats

Abstract: Enterogenic endotoxinemia was induced in 28 Wistar rats by means of intraperitoneal injection of 80 mg/kg carrageenan and intraduodenal administration of 5 x 10(10)/kg Escherichia coli bacteria and 10 mg/kg nebacetin. The control group A received 600 mg/kg albumin in addition via the duodenal probe, and the groups B, C and D received 20, 40 and 80 mg/kg lactoferrin, respectively. The therapeutic effect was investigated by determining the endotoxin activity in the plasma every hour. In addition, the bacterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…As has been addressed in experimental animals, Lf and Lf derivatives possess protective action against systemic bacterial infections [52,53,76] as well neutralizing properties in regard to endotoxemia [61] and intestinal damage [59] caused by LPS. Taking into account the multifactorial context of sepsis, Lf would not be recommendable as a single agent for the treatment of sepsis, but its permeabilizing and endotoxin neutralizing activities make it a potential adjunctive compound for the clinical treatment of that life threatening dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been addressed in experimental animals, Lf and Lf derivatives possess protective action against systemic bacterial infections [52,53,76] as well neutralizing properties in regard to endotoxemia [61] and intestinal damage [59] caused by LPS. Taking into account the multifactorial context of sepsis, Lf would not be recommendable as a single agent for the treatment of sepsis, but its permeabilizing and endotoxin neutralizing activities make it a potential adjunctive compound for the clinical treatment of that life threatening dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in the experimental model of enterogenic endotoxemia in rats infected enterically with E. coli and treated with antibiotics to promote LPS translocation, it was observed that Lf reduced LPS levels in plasma [52][53][54]. In another study with an animal model, Lf also showed the capacity to reduce inflammation at the intestinal level, thus conferring protection against diarrhea.…”
Section: Neutralizing Effects Of Lf On the Lps-induced Inflammatory Rmentioning
confidence: 97%
“…In one study of ETEC strain, the bacteria counts of ETEC in various sections of intestine is lower in the bLF treatment group than in the control group, implying the inhibitory effect of LF on the adherence of ETCE to the intestinal tract (Kawasaki et al 2000). LF is able to reduce the endotoxemia and bacterial translocation to mesenteric lymph nodes and peritoneal cavity after enteral challenge of E. coli (Nebermann et al 2001).…”
Section: Animal Studiesmentioning
confidence: 97%
“…Modulatory effects of either hLf or bLf, including derived Lfcins, on parameters associated with inflammation, has been evidenced in models of intestinal and systemic-related endotoxemia induced by LPS (also known as endotoxin) from Gram-negative enterobacteria [150,151]. These experimental models are intended to assess the impact of Lf at intestinal and systemic levels on inflammatory markers elicited by LPS that affect the gut barrier, bacterial translocation, diarrhea, tissue damage and endotoxic shock, among others [110,152,153,154,155]. In some cases, experimental assays with LPS administration encompass the use of zymosan, d -galactosamine ( d -GalN) or carrageenan to increase the sensibility of animals toward the toxic effects of low LPS doses [153,154].…”
Section: Lactoferrin As Anti-inflammatory In Infectious Diseasesmentioning
confidence: 99%
“…LFP20 elicited the expression of tight junction proteins involved in the regulation of intestinal permeability, i.e., zonula occludens-1, occludin and claudin-1, as well as decreased colonic apoptosis [110,152,153,154,155,156,157]. Protective action of hLf on the gut barrier function against the LPS-induced intestinal damage has also been described for hLf in in vitro cultures of Caco-2 cells and jejune segments of mice underwent LPS-endotoxemia [155,158].…”
Section: Lactoferrin As Anti-inflammatory In Infectious Diseasesmentioning
confidence: 99%